Transporters as Drug Targets. - Ecker, Gerhard F.; Clausen, Rasmus P.; Sitte, Harald (Weinheim, Germany : Wiley-VCH, 2017)
As opposed to other books on the topic, this volume is unique in also covering emerging transporter targets. Following a general introduction to the importance of targeting transporter proteins with drugs, the book systematically presents individual transporter classes and explains their pharmacology and physiology. The text covers all transporter families with known or suspected importance as drug targets, including neurotransmitter transporters, ABC transporters, glucose transporters and organic ion transporters. The final part discusses recent advances in structural studies of transport proteins, assay methods for transport activity, and the systems biology of transporters and their regulation. With its focus on drug development issues, this authoritative overview is required reading for researchers in industry and academia targeting transport proteins for the treatment of disease.
Keywords: Carrier proteins; Drug targeting; SCIENCE / Life Sciences / Biochemistry; Carrier proteins; Drug targeting; Drug carriers; Electronic books